A new class of hybrid anticancer agents inspired by the synergistic effects of curcumin and genistein: Design, synthesis, and anti-proliferative evaluation. Issue 20 (15th October 2015) - Chen, Qiao-Hong; Yu, Kevin; Zhang, Xiaojie; Chen, Guanglin; Hoover, Andrew; Leon, Francisco; Wang, Rubing; Subrahmanyam, Nithya; Addo Mekuria, Ermias; Harinantenaina Rakotondraibe, Liva
Graphical abstract: Abstract: Inspired by the synergistic effects of dietary natural products with different scaffolds on the inhibition of cancer cell proliferation, incorporation of central (1 E, 4 E )-1, 4-penta-dien-3-one linker (an optimal substitute for the central metabolically unstable diketone linker of curcumin), 1-alkyl-1 H -imidazol-2-yl (a promising bioisostere of terminal aryl group in curcumin), and chromone (the common pharmacophore in genistein and quercetin) into one chemical entity resulted in ten new hybrid molecules, 3-((1 E, 4 E )-5-(1-alkyl-1 H -imidazol-2-yl)-3-oxopenta-1, 4-dien-1-yl)-4 H -chromen-4-ones. They were synthesized through a three-step transformation using acid-catalyzed aldol condensation as key step. The WST-1 cell proliferation assay showed that they have greater anti-proliferative potency than curcumin, quercetin, and genistein on both androgen-dependent and androgen-independent human prostate cancer cells.